Barreras arancelarias y no arancelarias y su impacto en las exportaciones de café ecuatoriano. Caso de estudio Kawsana Coffee Cía. Ltda. - Cueva Martinez, Salomé Estefania (2025)
This Curricular Integration Project aims to analyze the impact of tariff and non-tariff barriers on Ecuadorian coffee exports at Kawsana Coffee Cía. Ltda., with the goal of contributing to its expansion and market positioning both nationally and internationally. International trade involves the exchange of goods between individuals or entities across countries, often subject to protective measures known as tariff barriers. The study employed a documentary methodology with a mixed approach, integrating qualitative and quantitative analysis. Various scientific methods—deductive, inductive, analytical, and synthetic—were applied, along with techniques such as observation, bibliographic research, surveys, and statistical analysis. The research examined Ecuador’s trade policies and agreements, identifying benefits for the coffee sector and Kawsana Coffee Cía. Ltda. Additionally, the study assessed the impact of tariff and non-tariff barriers on the company’s profitability. Based on the findings, market diversification strategies were proposed for both export and domestic distribution. The study concludes that tariff and non-tariff barriers do not pose a direct threat to the company’s exports. Instead, they have a positive impact, as they do not hinder coffee trade. However, expanding market reach and implementing brand awareness strategies could further enhance revenue and competitiveness.